2011
DOI: 10.1021/ma101926c
|View full text |Cite
|
Sign up to set email alerts
|

Radical Copolymerization of Isobutylene and Ethyl Acrylate with LiCB11Me12 Catalyst

Abstract: The radical homopolymerization of isobutylene (IB) is unusual but can be accomplished under catalysis with LiCB 11 (CH 3 ) 12 (1) in poorly coordinating solvents at ambient pressure and temperature. 1-3 It yields a novel highly branched form of polyisobutylene (b-PIB) with molecular weights in the thousands (up to ∼2.5 Â 10 4 ) according to GPC relative to polystyrene standards. Presently we examine the use of the LiCB 11 (CH 3 ) 12 catalyst with azo-tertbutane (ATB) radical initiator for the copolymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although interactions of ester group oxygen with the lithium cation are known and were described in the literature,12, 13 no precipitate was formed upon mixing the ABIPE solution with Li[CB 11 Me 12 ]. Thus, if any DCE soluble ABIPE–Li[CB 11 Me 12 ] complex was formed, it might still be catalytically active in the radical polymerization process, given that the presence of other esters, ethyl acetate, ethyl acrylate, poly (ethyl acrylate) does not prevent the lithium catalyzed radical polymerization of isobutylene 14. Using this azo initiator, monomer conversion reached about 6% after 24 h at 50 °C and only low‐molecular‐weight oligomers with M n < 1000 were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Although interactions of ester group oxygen with the lithium cation are known and were described in the literature,12, 13 no precipitate was formed upon mixing the ABIPE solution with Li[CB 11 Me 12 ]. Thus, if any DCE soluble ABIPE–Li[CB 11 Me 12 ] complex was formed, it might still be catalytically active in the radical polymerization process, given that the presence of other esters, ethyl acetate, ethyl acrylate, poly (ethyl acrylate) does not prevent the lithium catalyzed radical polymerization of isobutylene 14. Using this azo initiator, monomer conversion reached about 6% after 24 h at 50 °C and only low‐molecular‐weight oligomers with M n < 1000 were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Li + catalysis was first demonstrated a long time ago, when acrylonitrile containing a dissolved Li + salt was shown to undergo catalyzed radical polymerization (Scheme ). Later, it was shown for homopolymerization of acrylates and similar more activated monomers, and their copolymerization with less activated monomers, and it has been considered common knowledge for some time . Since alkenes activated for the complexation of Li + by the presence of suitable substituents with lone pairs, such as acrylonitrile or methacrylate, usually already undergo radical polymerization well in any event, metal ion catalysis is not critically needed and is of interest primarily as a possible source of stereocontrol.…”
Section: Li+ Catalyzed Radical Polymerizationmentioning
confidence: 99%
“…In the absence of the initiator or of the lithium salt, or in the presence of a radical inhibitor or a lithium complexing solvent, polymerization did not take place. 162,163 A closer look at the polymers formed from propylene (very highly branched, molar mass ∼30000 g•mol −1 ), 164 higher alkenes (molar mass below 1000 g•mol −1 ), 165 and most of all, isobutylene (very highly branched, see below), 161,165,166 as well as the copolymerization of isobutylene with ethyl acrylate (with up to ∼50 mol % IB content, highly branched, molar mass ∼30−50000 g•mol −1 ), 149,165 gradually revealed that it is difficult to reproduce some of the initially reported molar mass values. It ultimately became clear that the yields, molar masses, and at times even the structures of the polymers were a very sensitive function of the composition of the catalytic solution and that painstaking control was required to obtain reproducible results.…”
Section: Problemsmentioning
confidence: 99%
“…25 There have been some experiments demonstrating that the radical polymerization, especially for less activated monomers, could be promoted in the presence of lithium salts. 26,27 Very recently, direct controlled radical homopolymerizations of VEs were performed in water with LiOH as a mediator. 28 These results suggest that a specific interaction exists between Li + and CC, and perhaps to some extent, it would dominate over chain transfer steps and lead to highermolecular-weight PVEs.…”
Section: ■ Introductionmentioning
confidence: 99%